Seasonal and individual variation of semen quality parameters in crossbred (Alpine x Beetal) buck - NARWADE, B. M.; MOHANTY, TUSHAR KUMAR; BHAKAT, MUKESH; RAHIM, ABDUL (Indian Journal of Dairy Science, 2018)
Present investigation was conducted on five crossbred buck to assess individual performance and seasonal effect on semen quality parameters. Semen was collected twice a week using artificial vagina and evaluated for its physical characteristics. Data on 625 ejaculates from five adult bucks (125×5) during different season were recorded and analyzed for semen quality parameters. The overall mean ejaculate volume, mass activity (MA), progressive motility, live sperm, sperm concentration, hypo-osmotic swelling test (HOST) and intact acrosome were 1.09±0.01ml, 3.29±0.03%, 76.46±0.31%, 78.65±0.21% 2.97´109/ml, 69.31±0.21% and 93.89±0.09%, respectively. Analysis revealed that, buck had significant (p